Automated Hydroponics System using the Internet of Things - Yulianto, Dinan; Nugraha, Abiema Febrian; Rahani, Faisal Fajri (DPTE FT UNY, 2024)
The Indonesian government has instituted urban farming regulations to bolster food security and catalyze economic growth. However, implementing urban farming initiatives across various regions of Indonesia is expected to face challenges in the quality and availability of arable land, along with deficiencies in community knowledge. Hydroponics represents a sustainable agricultural approach proposed as a viable solution to address land quantity and quality limitations. This paper presents the comprehensive design and deployment of an automatic monitoring and control system tailored to hydroponic parameters using Internet of Things (IoT) technologies. This system integrates web technology with a NodeMCU microcontroller and sensor devices, such as DHT22 Sensor, SEN011 Sensor, TDS SEN0244 Sensor, DS18820 Sensor, and HC-SR04 Sensor. Web technology was successfully built to display eight hydroponic environmental data variables in real time, including nutrient levels, water pH, water level, water temperature, air temperature, air humidity, and pump performance status. The pH threshold value of water on a scale of 5.0 to 6.5 will automatically control the pH pump, the nutrient threshold value on a scale of 500 to 800 ppm will automatically control the nutrient pump, and the water height threshold value on a scale of 30 to 10 cm will automatically control the water pump. Through web technology, users can also intervene in system performance based on natural plant conditions. The entire system functionality was tested with 25 scenarios through a black box test approach, demonstrating that the hydroponic environment was monitored and controlled efficiently.